Activation of Lactate Receptor Positively Regulates Skeletal Muscle Mass in Mice - Ohno, Y; Nakatani, M; Ito, T; Matsui, Y; Ando, K; Suda, Y; Ohashi, K; Yokoyama, S; Goto, K (Physiological research, 2023)
G protein-coupled receptor 81 (GPR81), a selective receptor for lactate, expresses in skeletal muscle cells, but the physiological role of GPR81 in skeletal muscle has not been fully elucidated. As it has been reported that the lactate administration induces muscle hypertrophy, the stimulation of GPR81 has been suggested to mediate muscle hypertrophy. To clarify the contribution of GPR81 activation in skeletal muscle hypertrophy, in the present study, we investigated the effect of GPR81 agonist administration on skeletal muscle mass in mice. Male C57BL/6J mice were randomly divided into control group and GPR81 agonist-administered group that received oral administration of the specific GPR81 agonist 3-Chloro-5-hydroxybenzoic acid (CHBA). In both fast-twitch plantaris and slow-twitch soleus muscles of mice, the protein expression of GPR81 was observed. Oral administration of CHBA to mice significantly increased absolute muscle weight and muscle weight relative to body weight in the two muscles. Moreover, both absolute and relative muscle protein content in the two muscles were significantly increased by CHBA administration. CHBA administration also significantly upregulated the phosphorylation level of p42/44 extracellular signal-regulated kinase-1/2 (ERK1/2) and p90 ribosomal S6 kinase (p90RSK). These observations suggest that activation of GRP81 stimulates increased the mass of two types of skeletal muscle in mice in vivo. Lactate receptor GPR81 may positively affect skeletal muscle mass through activation of ERK pathway.
Keywords: Muscle, Skeletal; Animals; Mice, Inbred C57BL; Male; hypertrofie; Muscle Fibers, Skeletal; Receptors, G-Protein-Coupled; kosterní svaly; mužské pohlaví; myši inbrední C57BL; Lactic Acid; myši; Hypertrophy; zvířata; kosterní svalová vlákna; receptory spřažené s G-proteiny; kyselina mléčná; Mice